OPTIMALISASI PEMANFAATAN SUMBER DAYA AIR DALAM WAWASAN KETAHANAN BANGSA: SEBUAH ULASAN: SEBUAH ULASAN - Muchamad, Arief Nur; Prajati, Gita Prajati; Mulyani, Tri; Febrion, Churchil (JURNAL KEBANGSAAN RI, 2025)
Water plays many important roles in various sectors of life. The concept of water security is a form of social security that can guarantee access to water for communities and individuals. Therefore, this study aims to review journals, articles, and scientific papers that discuss water resource management and conservation and their relationship to national awareness and security. The research was conducted using a literature review method with a narrative approach. The results of the study show that sustainable development requires the integration of water resource conservation and policies that support effective and equitable management. The concept of Smart Water Management (SWM) based on local wisdom can be used as a method of water resource management. One of the steps to achieve national resilience is by securing water resilience. The results of the evaluation of water resource conservation development show that the implementation of water resource conservation in Indonesia has not been running well.